Proceedings of the 10th Asia Pacific Conference on Computer Human Interaction 2012
DOI: 10.1145/2350046.2350101
|View full text |Cite
|
Sign up to set email alerts
|

Drawing and acting as user experience research tools

Abstract: This paper discusses the use of participant-generated drawings and drama workshops as user experience research methods. In spite of the lack of background literature on how drawings can generate useful insights on HCI issues, drawings have been successfully used in other research fields. On the contrary, drama workshops seem to be increasingly popular in recent participatory design research. After briefly introducing such previous work, three case studies are presented, illustrating the use of drawing and dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…When conducting international research or design work, cultural and linguistic differences may need to be addressed. Fleury (2012) found when conducting studies using drawings and drama workshops that Japanese (child) participants went into greater detail than their American counterparts, with the conclusion being drawn that 'these differences are explained by cultural clues of how children are raised in both societies'. The authors also observed differences between Japanese and Danish participants when investigating the emotional relationship between users and their mobile phones and TVs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When conducting international research or design work, cultural and linguistic differences may need to be addressed. Fleury (2012) found when conducting studies using drawings and drama workshops that Japanese (child) participants went into greater detail than their American counterparts, with the conclusion being drawn that 'these differences are explained by cultural clues of how children are raised in both societies'. The authors also observed differences between Japanese and Danish participants when investigating the emotional relationship between users and their mobile phones and TVs.…”
Section: Discussionmentioning
confidence: 99%
“…Drama appears to be useful to encourage participation around unforeseen futures or new technologies, and can bridge the distance between user and designer. It also appears most useful in situations where communication would otherwise be difficult, such as in international workshops where language barriers may be an issue (Fleury, 2012). Acting sessions can facilitate the communication of emotions which are difficult to convey with words (Mehto et al, 2006).…”
Section: Figure 4 Actors Perform To Stakeholders Who Provide Input Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand-drawn sketches are lightweight and easy to create and by varying the fidelity of sketches they can be an integral part of all stages of HCI research and the design process [10]. Such flexibility makes them a valuable tool that can increase access; break down boundaries to concept expression; support the thinking process; and communicate ideas to others [12]. As such, hand-drawn sketching has trickled into HCI researcher's everyday practices -with a particular focus on the gathering or reflecting on user research data, designing of novel user experiences, [6, 8, 3, 7 & 9].…”
Section: Motivationmentioning
confidence: 99%
“…Describing possible futures and enacting scenarios are known to represent a multi-faceted design tool [1]. By acting, stakeholders can simulate the targeted users' experiences and feelings, which can contribute to understanding challenges and designing services and products [6,18]. The experiences from previous games are condensed, empathy for the users and the use-situations is developed, and also the design concept is elaborated while the players take on roles, create scenarios, and act them out in physical space such as kitchen.…”
Section: ) the Scenario Gamementioning
confidence: 99%